Novel Secreted Peptides From Rhizopus arrhizus var. delemar With Immunomodulatory Effects That Enhance Fungal Pathogenesis - Soliman, Sameh S. M.; El-Labbad, Eman M.; Abu-Qiyas, Ameera; Fayed, Bahgat; Hamoda, Alshaimaa M.; Al-Rawi, Ahmed M.; Dakalbab, Salam; El-Shorbagi, Abdel-Nasser A.; Hamad, Mawieh; Ibrahim, Ashraf S.; Mohammad, Mohammad G. (Frontiers in Microbiology, 2022)
Secreted fungal peptides are known to influence the interactions between the pathogen ‎and host innate immunity. The aim of this study is to screen and evaluate secreted peptides from ‎the fungus Rhizopus delemar for their immunomodulatory activity. By using mass spectrometry ‎and immuno-informatics analysis, we identified three secreted peptides CesT (S16), Colicin ‎‎(S17) and Ca2+/calmodulin-dependent protein kinase/ligand (CAMK/CAMKL) (S27). Culturing ‎peripheral blood-derived monocytic macrophages (PBMMs) in the presence of S16 or S17 caused ‎cell clumping, while culturing them with S27 resulted in the formation of spindle-shape cells. ‎S27-treated PBMM showed cell cycle arrest at G0 phase and exhibited alternatively ‎activatedmacrophage phenotype with pronounced reduction in scavenger receptors CD163 and ‎CD206. Homology prediction indicated that IL-4/IL-13 is the immunomodulatory target of S27. ‎Confirming this prediction, S27 initiated macrophages activation through phosphorylation of ‎STAT-6, and STAT-6 inhibition reversed the activity of S27 and reduced the formation of ‎spindle-shaped PBMMs. Lastly, S27 treatment of PBMMs was associated with an influence on ‎the expression of iron regulatory genes (e.g. hepcidin, ferroportin, transferrin receptor 1 and ‎ferritin) in a pattern that is consistent with increased cellular iron release, a condition known to ‎enhance Rhizopus infection. Collectively, R. delemar secretes peptides with immunomodulatory ‎activities that support fungal pathogenesis, while targeting IL-4/IL-13R, STAT-6 axis is a ‎potential therapeutic approach to enhance their PBMM-mediated fungal phagocytosis. This ‎represents a potential new approach to overcome lethal mucormycosis.‎